The AOR-Base Splitting Modified Fixed Point Iteration for Solving Absolute Value Equations (Communications in Mathematical Research, 2024)
Recently, Yu et al. presented a modified fixed point iterative (MFPI)method for solving large sparse absolute value equation (AVE). In this paper,we consider using accelerated overrelaxation (AOR) splitting to develop themodified fixed point iteration (denoted by MFPI-JS and MFPI-GSS) methodsfor solving AVE. Furthermore, the convergence analysis of the MFPI-JS andMFPI-GSS methods for AVE are also studied under suitable restrictions on theiteration parameters, and the functional equation between the parameter $τ$ andmatrix $Q.$ Finally, numerical examples show that the MFPI-JS and MFPI-GSSare efficient iteration methods.